Work Family Conflict dan Subjective Well-Being pada Polisi Wanita - Sophia Christy; Ka Yan (Humanitas (Jurnal Psikologi), 2020)
The purpose of this research is to examine the correlation between Work Family Conflict and Subjective Well-being and married police woman who have a child as the subject. The measuring instrument that has been used in this research is Work Family Conflict created Carlson, Kacmar, & William (2000) and translated by Kuntari (2018). There are two measuring instrument of Subjective Well-being; SWLS constructed by Diener, Emmons, Larsen & Griffin (1985) and SPANE constructed by Diener (2009), both of instrument has been translated by Gunawan (2018). Data that have been collected, processed by using SPSS 25 and Spearman correlation. The result of correlation number in this research is 0,796 and stated that there is no correlation between Work Family Conflict and Subjective Well-being. Keywords: Work Family Conflict, Subjective Well-being